Effectiveness of two and three doses of COVID-19 mRNA vaccines against infection, symptoms, and severity in the pre-omicron era: A time-dependent gradient - Layan Sukik (6619544) (2024)
Background Vaccines were developed and deployed to combat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This study aimed to characterize patterns in the protection provided by the BNT162b2 and mRNA-1273 mRNA vaccines against a spectrum of SARS-CoV-2 infection symptoms and severities. Methods A national, matched, test-negative, case-control study was conducted in Qatar between January 1 and December 18, 2021, utilizing a sample of 238,896 PCR-positive tests and 6,533,739 PCR-negative tests. Vaccine effectiveness was estimated against asymptomatic, symptomatic, severe coronavirus disease 2019 (COVID-19), critical COVID-19, and fatal COVID-19 infections. Data sources included Qatar's national databases for COVID-19 laboratory testing, vaccination, hospitalization, and death. Results Effectiveness of two-dose BNT162b2 vaccination was 75.6% (95% CI: 73.6–77.5) against asymptomatic infection and 76.5% (95% CI: 75.1–77.9) against symptomatic infection. Effectiveness against each of severe, critical, and fatal COVID-19 infections surpassed 90%. Immediately after the second dose, all categories—namely, asymptomatic, symptomatic, severe, critical, and fatal COVID-19—exhibited similarly high effectiveness. However, from 181 to 270 days post-second dose, effectiveness against asymptomatic and symptomatic infections declined to below 40%, while effectiveness against each of severe, critical, and fatal COVID-19 infections remained consistently high. However, estimates against fatal COVID-19 often had wide 95% confidence intervals. Analogous patterns were observed in three-dose BNT162b2 vaccination and two- and three-dose mRNA-1273 vaccination. Sensitivity analyses confirmed the results. Conclusion A gradient in vaccine effectiveness exists and is linked to the symptoms and severity of infection, providing higher protection against more symptomatic and severe cases. This gradient intensifies over time as vaccine immunity wanes after the last vaccine dose. These patterns appear consistent irrespective of the vaccine type or whether the vaccination involves the primary series or a booster. Other Information Published in: Vaccine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.vaccine.2024.04.026 Additional institutions affiliated with: Hamad Bin Khalifa University